Science vs. religion: what scientists really think - Ecklund, Elaine Howard (Oxford University Press, 2012)
"That the longstanding antagonism between science and religion is irreconcilable has been taken for granted. And in the wake of recent controversies over teaching intelligent design and the ethics of stem-cell research, the divide seems as unbridgeable as ever. In Science vs. Religion, Elaine Howard Ecklund investigates this unexamined assumption in the first systematic study of what scientists actually think and feel about religion. In the course of her research, Ecklund surveyed nearly 1,700 scientists and interviewed 275 of them. She finds that most of what we believe about the faith lives of elite scientists is wrong. Nearly 50 percent of them are religious. Many others are what she calls 'spiritual entrepreneurs, ' seeking creative ways to work with the tensions between science and faith outside the constraints of traditional religion. The book centers on vivid portraits of 10 representative men and women working in the natural and social sciences at top American research universities"--Page 2 of cover